A study of aspects of utilization of tallow by young milk-fed calves : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Agricultural Science at Massey University - Betteridge, Keith (Massey University, 1973)
1. Three groups of 4 Friesian bull calves were individually fed from 7 days of age on one of the following diets; (L) - Butter-milk powder (B.M.P.) to promote 0.45 kg liveweight gain (LWG)/day; (H) - B.M.P. to promote 0.67 kg LWG/day; (HT) - B.M.P. supplemented with beef tallow to promote 0.67 kg LWG/day. The diets, reconstituted to 15% dry matter (d.m.), were fed. in direct proportion to the animal's liveweight at the beginning of each of the 3 consecutive 10-day experimental periods. N.B. Skim milk powder (S.M.P.), initially used as the basal diet, was subsequently replaced, by B.M.P. and the trial was restarted. 2. Daily faecal d.m. consistency was subjectively scored on a 0 - 5 sca1e. Quantitative measurements were made in conjunction with the faecal collections for the nitrogen balance. 3. Nitrogen balance data were collected from of the 4 calves, in each group during the last 5 days, and energy balance data during the last 2 days of each period. 4. The addition of 4% tallow (d.m. basis) significantly reduced the incidence of scours (p<0.01) in calves fed a basal diet of either S.M.P. or B.M.P. 5. Mean LWG's of calves on treatments L, H and- HT were respectively 0.57, 0.73 ard 0.62 kg/day; these differences were not statistica1ly significant (p > 0.1). 6. The calves on treatment H, although having the highest urinary nitrogen excretion (p < 0.05), retained the most nitrogen (g/kg 0.75/day) (p < 0.05). The ratio of digested nitrogen retained : M.E. intake was highest for the calves fed the tallow supplement. This suggests that energy rather than protein is the factor most limiting protein deposition in calves fed solely on B.M.P. 7. During the second and third periods diets H and HT promoted a significantly greater retention of energy than did diet L (p < 0.01). The percentage of energy retained as fat tended to be higher in calves on treatment H. 8. The maintenance enerey requirement for a 50 kg calf was estimated to be 53.5 kcals D.E./kg liveweight. The efficiency of utilisation of M.E. for growth was found to be 78%.
Keywords: Friesian calves; Bull calves; Calf feed